Structural and Biochemical Characterization of Cinnamoyl-CoA Reductases. Issue 2 (12th December 2016) - Sattler, Steven A.; Walker, Alexander M.; Vermerris, Wilfred; Sattler, Scott E.; Kang, ChulHee
Abstract : In-depth investigation for CCRs from Sorghum bicolor provides information about the critical residuesfor substrate preference among CCRs. Abstract: Cinnamoyl-coenzyme A reductase (CCR) catalyzes the reduction of hydroxycinnamoyl-coenzyme A (CoA) esters using NADPH to produce hydroxycinnamyl aldehyde precursors in lignin synthesis. The catalytic mechanism and substrate specificity of cinnamoyl-CoA reductases from sorghum ( Sorghum bicolor ), a strategic plant for bioenergy production, were deduced from crystal structures, site-directed mutagenesis, and kinetic and thermodynamic analyses. Although SbCCR1 displayed higher affinity for caffeoyl-CoA or p -coumaroyl-CoA than for feruloyl-CoA, the enzyme showed significantly higher activity for the latter substrate. Through molecular docking and comparisons between the crystal structures of the Vitis vinifera dihydroflavonol reductase and SbCCR1, residues threonine-154 and tyrosine-310 were pinpointed as being involved in binding CoA-conjugated phenylpropanoids. Threonine-154 of SbCCR1 and other CCRs likely confers strong substrate specificity for feruloyl-CoA over other cinnamoyl-CoA thioesters, and the T154Y mutation in SbCCR1 led to broader substrate specificity and faster turnover. Through data mining using our structural and biochemical information, four additional putative CCR genes were discovered from sorghum genomic data. One of these, SbCCR2, displayed greater activity toward p -coumaroyl-CoA than did SbCCR1, which could imply a role in the synthesis of defense-related lignin. Taken together, these findings provide knowledge about critical residues and substrate preference among CCRs and provide, to our knowledge, the first three-dimensional structure information for a CCR from a monocot species.